2021
DOI: 10.1007/s11258-021-01117-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leaf water extracts of four Asteraceae alien invasive plants on germination performance of Lactuca sativa L. under acid deposition

Abstract: Allelopathy of alien invasive plants (AIP) on plant germination performance is essential for their successful invasion. However, the allelopathy of AIP may be reformed or even strengthened under acid deposition. AIP in Asteraceae covers the uppermost number of AIP species at the family level presently in China. It is necessary to estimate the allelopathy of multiple Asteraceae AIP under acid deposition to address the mechanism driving their successful invasion, especially under acid deposition. However, resear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Moreover, the mean lettuce seed germination time increased in response to the aqueous A. frigida extracts but decreased in response to those of A. splendens and S. chamaejasme (Figure 1c). and has high germination rates and rapid growth [34,43,44]. The aims of this study were to (1) clarify whether aqueous shoot extracts of donor plants have hormesis effects, (2) compare the allelopathic effects among the donor plants, (3) determine whether donor plant soaking time affects allelopathy, and (4) screen suitable recipient plant germination characteristics of lettuce to evaluate allelopathic potential.…”
Section: Effects Of Aqueous Herb Extracts On Lettuce Seed Germinationmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the mean lettuce seed germination time increased in response to the aqueous A. frigida extracts but decreased in response to those of A. splendens and S. chamaejasme (Figure 1c). and has high germination rates and rapid growth [34,43,44]. The aims of this study were to (1) clarify whether aqueous shoot extracts of donor plants have hormesis effects, (2) compare the allelopathic effects among the donor plants, (3) determine whether donor plant soaking time affects allelopathy, and (4) screen suitable recipient plant germination characteristics of lettuce to evaluate allelopathic potential.…”
Section: Effects Of Aqueous Herb Extracts On Lettuce Seed Germinationmentioning
confidence: 99%
“…Therefore, lettuce growth fitness may be substantially attenuated in response to allelopathy mediated by the foregoing herbs. The allelochemicals may poison weak seeds, impede nutrient absorption, and hinder seedling growth and development [44]. On the contrary, the donor aqueous extracts had positive influences on lettuce shoot length and biomass as well as leaf dimensions.…”
Section: Effects Of Extract Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Invasion by alien plant species causes a significant effect on the ecosystem. An experiment performed by Cheng et al (2021) using four Asteraceae alien invasive plants (AIP), i.e., Conyza canadensis, Erigeron annuus, Aster subulatus, and Bidens pilosa, on germination of Lactuca sativa revealed that SAR of high acidity (pH 4.5) increases the process of invasion and allelopathy on the germination and root length of L. sativa.…”
Section: Growth and Yieldmentioning
confidence: 99%